Metabolic and hormonal studies in patients with essential hypertension. Issue 11 (November 1977) - Januszewicz, W; Ciswicka-Sznajderman, M; Wocial, B; Sznajderman, M; Ignatowska-Switalska, H; Berent, H; Zukowska-Grojec, Z; Feltynowski, T
Abstract : In 106 patients with essential hypertension and different plasma renin activity several hormonal and metabolic factors were studied: urinary excretion of catecholamines, blood levels of cholesterol and triglycerides, levels of glycaemia and insulinaemia after glucose load and plasma fibrinolytic activity. The plasma renin activity in 46.2 percent of patients was normal, whereas in 25.5 percent it was low, and in 28.3 percent it was high. In patients with high plasma renin activity the excretion of noradrenaline and adrenaline was relatively high while that of dopamine was low. Significantly lower triglyceride levels were found in patients with low plasma renin activity in comparison with those with high and normal plasma renin activity. There was also a statistically significant difference in the euglobulin lysis time which was shorter in patients with low and longest in patients with normal plasma renin activity. The results of the study show that patients with different plasma renin activity may also differ in some hormonal and metabolic values.